Bursting water balloons. (4th September 2014) - Lund, Hugh M.; Dalziel, Stuart B.
Abstract: The impact and rupture of a water-filled latex balloon on a flat, rigid surface is investigated using high-speed photography. Three distinct stages of the flow are observed, for which physical explanations are given. As the balloon lands and deforms, waves are formed on the balloon's surface for which the restoring force is tension in the latex. These waves are shown to closely obey linear potential theory for constant surface tension. Should the balloon rupture, a crack forms, from which the membrane retracts. Spray is simultaneously ejected from the water's surface, a consequence of a shear instability in the wake behind the retracting membrane. At later times, a larger-scale growth of the interfacial amplitude is observed, for which the generation mechanism is momentum in the water due to the preburst waves. However, it is argued that this is also a manifestation of the same mechanism that drives Richtmyer–Meshkov instability (RMI). Further, it is shown experimentally that this growth of the interface may also occur when there is no density difference across the balloon, a situation that does not arise for the standard RMI. An analytical model is then derived to predict the interfacial growth for such an interface, and is shown to predict the asymptotic growth rate of the interface accurately.